2020
DOI: 10.26710/jbsee.v6i2.1092
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Public Debt Burden and Health Expenditure in Sub-Saharan African Countries: The Role of Institutional Quality

Abstract: The historically lower level of public health expenditure of sub-Saharan African (SSA) countries could be partly explained by the mounting debt burden of this region. This consumes a sizable proportion of their domestic resources to debt servicing and potentially decreases their overall budgetary allocations to various sectors in the economy and health expenditure in particular. Using the Generalized Method of Moments (GMM) approach on a sample of 43 sub-Saharan African countries, we examined the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The study reported, among other things, that public debt lessens human development. Likewise, Said and Morai (2020) applied the GMM technique to report a negative connection between debt accumulation and health spending in SSA nations. A recent study by Sadiq, Wen et al (2022) for 16 OECD nations between 1990 and 2019 reported that human development is hampered by public debt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study reported, among other things, that public debt lessens human development. Likewise, Said and Morai (2020) applied the GMM technique to report a negative connection between debt accumulation and health spending in SSA nations. A recent study by Sadiq, Wen et al (2022) for 16 OECD nations between 1990 and 2019 reported that human development is hampered by public debt.…”
Section: Literature Reviewmentioning
confidence: 99%